THE USE OF MELD SCORE (MODEL FOR END-STAGE LIVER DISEASE) AND DERIVATIVES IN CARDIAC TRANSPLANTATION - MORAES,Ana Claudia Oliveira de (2018)
ABSTRACT Introduction: Heart transplantation is still the best therapeutic alternative for the treatment of end-stage heart failure. The use of criteria that consider the complications associated with this procedure can guarantee a better evaluation of the recipient and prepare the team for possible unsatisfactory post-transplant results. The use of the MELD score has been expanded to evaluate cirrhotic patients undergoing various procedures, including cardiac transplantation. Objective: To analyze the knowledge on MELD score and its derivatives to the prognosis of patients with end-stage heart failure considered for heart transplantation. Method: Was carried out an integrative review of the publications of the last ten years in Pubmed and Lilacs databases, using the descriptors “heart transplantation”, “liver disease” and “prognosis”. From the total of 111 articles found, six were selected and composed the sample. Results: The MELD-XI score (eXcluding INR) was the most analyzed in the studies due to the exclusion of INR, since many patients with heart failure use anticoagulants, which may alter their value. MELD and derivatives were associated with unsatisfactory results in cardiac transplantation. Conclusion: The MELD score can be considered as a good predictor for heart transplantation; however, there are still few studies that make this correlation.